+0

# Need help!

+5
86
1
+359

If f(x)=5x-12, find a value for x so that f^{-1}(x)=f(x+1).

MIRB16  Jul 23, 2017

#1
+4777
+1

f(x)  =  5x - 12

Let's say...

y  =  5x - 12

Now solve this equation for  x  .

y + 12  =  5x

(y + 12) / 5  =  x

To get the inverse function, swap  x  and  y  . Instead of  " y "  I put   " f-1(x) "

f-1(x)  =  (x + 12) / 5

And we want to find what  x  value makes...

f-1(x)  =  f(x + 1)

That is...

(x + 12) / 5  =  5(x + 1) - 12

Multiply both sides by  5  .

x + 12  =  25(x + 1) - 60

x + 12  =  25x + 25 - 60

Subtract  25x  from both sides and subtract  12  from both sides.

x - 25x  =  -12 + 25 - 60

-24x  =  -47

x  =  47/24

hectictar  Jul 23, 2017
Sort:

#1
+4777
+1

f(x)  =  5x - 12

Let's say...

y  =  5x - 12

Now solve this equation for  x  .

y + 12  =  5x

(y + 12) / 5  =  x

To get the inverse function, swap  x  and  y  . Instead of  " y "  I put   " f-1(x) "

f-1(x)  =  (x + 12) / 5

And we want to find what  x  value makes...

f-1(x)  =  f(x + 1)

That is...

(x + 12) / 5  =  5(x + 1) - 12

Multiply both sides by  5  .

x + 12  =  25(x + 1) - 60

x + 12  =  25x + 25 - 60

Subtract  25x  from both sides and subtract  12  from both sides.

x - 25x  =  -12 + 25 - 60

-24x  =  -47

x  =  47/24

hectictar  Jul 23, 2017

### 15 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details